Driving Workforce Productivity of Banking Employee : The Moderating Role of Motivation in the Work Environment - Sriani, Putu Putri Indah; Heryanda, Komang Krisna (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to examine the influence of the work environment on employee productivity, with work motivation acting as a moderating variable at BPD Bali Bank. A quantitative approach was employed using data collected from 63 employees through a Likert-scale questionnaire. The analysis was conducted using Moderated Regression Analysis (MRA). The findings indicate that a supportive work environment positively affects employee productivity, and that work motivation strengthens this relationship. These results highlight the importance of integrating motivational strategies—such as training, reward systems, and career development programs—with efforts to improve the work environment. Enhancing both factors simultaneously can contribute to higher levels of employee productivity and overall organizational performance.